2019
DOI: 10.1097/dcc.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Educational Program on the Knowledge and Attitude About Pain Assessment and Management Among Critical Care Nurses

Abstract: Background Pain assessment and management are imperative parts of nursing care and considered as one of the most fundamental patient rights. The role of pain management education is well established in improving knowledge and attitude among nurses. Objectives This study aims to evaluate the impact of pain management educational program on the knowledge and attitudes of intensive care unit (ICU) staff nurses toward pain assessment and management. The bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A recent study aimed to assess the effectiveness of pain management education program among nurses working in ICU. The study found that the program was effective in increasing the knowledge level and attitudes of ICU nurses to be more positive toward pain management the (16).…”
Section: Discussionmentioning
confidence: 92%
“…A recent study aimed to assess the effectiveness of pain management education program among nurses working in ICU. The study found that the program was effective in increasing the knowledge level and attitudes of ICU nurses to be more positive toward pain management the (16).…”
Section: Discussionmentioning
confidence: 92%
“…Other studies showed variation in the topics covered in pain education 24,[26][27][28] ; however, there was a consensus about the importance of training and education on pain-related topics to improve nurses' knowledge and practices in pain assessment and management. 29,30 In a study conducted in 2012 by Al Qadire and Al Khalaileh, 31 it was found that 52% of Jordanian nurses reported no previous pain education in the last 5 years. It must be pointed out that 54% of the ICU nurses in this study perceived "ongoing education on pain" as an enabler of pain assessment and management.…”
Section: Discussionmentioning
confidence: 99%
“…Kizza et al 27 have shown that very few nurses had ever read any pain assessment and management guidelines or received education on practice guidelines for pain assessment and management, while Rose et al 28 found that pain assessment methods and tools were the topics covered for the greatest number of ICU nurses. Other studies showed variation in the topics covered in pain education 24,26‐28 ; however, there was a consensus about the importance of training and education on pain‐related topics to improve nurses' knowledge and practices in pain assessment and management 29,30 . In a study conducted in 2012 by Al Qadire and Al Khalaileh, 31 it was found that 52% of Jordanian nurses reported no previous pain education in the last 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, from the previous studies using learning is a vital method to find a solution for pain management problems. One research conducted in the Kingdom of Saudi Arabia in the critical care area to assess the impact of educational programmes on the nurses’ knowledge and attitude toward pain management, and the results showed substantial improvement in the nurses’ knowledge and attitude toward pain management (Issa et al, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%